In vitro cytotoxic activity of five commercial samples of Tribulus terrestris Linn in Espírito Santo (Brazil) - Claudio Costa Oliveira Filho; Edgar Hell Kampke; Thais Souza Vargas; Nathacha Andrade Salustriano; Rodrigo Scherer; Marcio Fronza; Bianca Prandi Campagnaro (Universidade de São Paulo, 2018)
ABSTRACT The objective was to investigate the total saponin and protodioscin concentrations and the cytotoxicity in vitro, of five samples of the plant Tribulus terrestris, commercially available in the metropolitan region of Vitória - Espirito Santo, Brazil, and to compare them with the aqueous extract of the plant. The chromatographic profile and quantification of protodioscin in commercial samples and plant extract were evaluated by LC-MS/MS. The percentage of total saponins were determined by the colorimetric method. Extracts and protodioscin cytotoxicity were analyzed by the MTT assay in three cell lineages: fibroblasts (L929), ovarian cancer (Ovcar3) and murine hepatoma (Hepa1c1c7). All extracts displayed high levels of total saponins (207.2 to 780.3 mg g-1 of dry extract). The chromatographic profile revealed a wide diversity of compounds, and the saponin protodioscin was detected in only two extracts. One extract displayed high cytotoxicity, with IC50 values of 157.0, 38.2 and 7.4 µg mL-1 for the Ovcar3, Hepa1c1c7 and L929 cell lines, respectively. The other extracts displayed cytotoxic effects only at concentrations equal to or greater than 125.0 µg mL-1. Surprisingly, the most cytotoxic extract displayed the highest protodioscin concentration. Therefore, it is suggested that these products be marketed with caution, and followed-up by a certified healthcare professional.